The Importance and Role of Public Relations In The Marketing Department at Mangkuluhur ARTOTEL Suites - Fitran, Habibillah; Ridha, Mohammad (Jurnal Vokasi Indonesia, 2024)
ABSTRACT The purpose of writing this research is to explain the role of Public Relations in the Marketing Communication Department regarding how to improve brand image, improve marketing and advertising to be more optimal, publish various information and promotions at Mangkuluhur ARTOTEL Suites through various information media and social media, and how to respond to customer complaints, as well as obstacles that occur in hotels related to various customer complaints and poor communication by several individuals within the hotel employees are also accompanied by appropriate solutions. To complete this research, the author collected data by conducting observations accompanied by interviews with the Marketing Communication Department Manager and the results showed that the role of a public relations person is very important in achieving the success of a hotel industry, especially in terms of communication with various stakeholders in the industry. Keywords: brand image, promotion, marketing, advertising, social media, hotel.